2004
DOI: 10.1007/s00415-004-0442-z
|View full text |Cite
|
Sign up to set email alerts
|

Low CSF hypocretin-1/orexin-A associated with hypersomnia secondary to hypothalamic lesion in a case of multiple sclerosis

Abstract: Sirs: Hypocretins/orexins are hypothalamic neuropeptides that are related to sleep-wake regulation [1,10]. It has been reported that cerebrospinal fluid (CSF) hypocretin-1/orexin-A level is dramatically decreased in narcolepsy-cataplexy [4,8,9,11]. Narcolepsy is also known to occur secondary to hypothalamic lesions caused by tumors, stroke, multiple sclerosis (MS) or acute disseminated encephalomyelitis, and the CSF hypocretin-1 level is decreased in some of them [5][6][7]12]. However, it remains unclear wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 11 publications
0
30
0
1
Order By: Relevance
“…As in our study, in a prospective study of 70 MS patients, none fulfilled the polysomnographic criteria of narcolepsy despite several patients suffered from symptoms suggestive of narcolepsy, including a high frequency of sleep attacks, cataplexy, and sleep paralysis [2]. The lesions are often localized to the hypothalamus and cerebrospinal fluid hypocretin-1 levels are low, but may be reversible [37,39,43]. Both diseases have common genetic links since 95% of narcoleptics and 50–60% of MS patients demonstrate positivity to the DR haplotype DR2 [44].…”
Section: Discussionmentioning
confidence: 99%
“…As in our study, in a prospective study of 70 MS patients, none fulfilled the polysomnographic criteria of narcolepsy despite several patients suffered from symptoms suggestive of narcolepsy, including a high frequency of sleep attacks, cataplexy, and sleep paralysis [2]. The lesions are often localized to the hypothalamus and cerebrospinal fluid hypocretin-1 levels are low, but may be reversible [37,39,43]. Both diseases have common genetic links since 95% of narcoleptics and 50–60% of MS patients demonstrate positivity to the DR haplotype DR2 [44].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of episodes of cataplexy and HLA negativity in our patient may suggest that the disease did not occur primarily. Although a similar sleep abnormality was observed in a case of MS with hypothalamic lesions [9], the absence of anti-AQP4 antibody had been proven (personal communication).…”
mentioning
confidence: 87%
“…The symptoms of narcolepsy are also known to occur secondary to hypothalamic lesions of various neurological conditions, such as brain tumors [6] and multiple sclerosis (MS) [2,9].…”
mentioning
confidence: 99%
“…Involvement of hypothalamus on MRI is associated with increased fatigue [65]. There has been a report of hypersomnia and low orexin-1 level due to a demyelinating lesion in the hypothalamus [66]. However, studies in larger groups of patients with relapsing remitting MS have found cerebrospinal fluid levels of hypocretin-1 to be normal, and they didn't observe a correlation with hypersomnolence [67].…”
Section: Sleep Disordersmentioning
confidence: 99%